Resistance in educational leadership, management and administration - Heffernan, Amanda; Thomson, Pat, 1948-; Blackmore, Jill (New York : Routledge, 2024)
"This edited volume brings together a range of perspectives on Educational Leadership, Management and Administration (ELMA) and various theories of resistance or compliance along with how policy and politics play out in school communities. The book makes a significant contribution to debates around theorising educational leadership and the implications of discourses on schooling and the politics of education. It brings together a broad array of international scholars to examine theories of resistance in ELMA and establish a resistance-oriented agenda for critical ELMA research that promotes change and diverse ideas about leadership. Using both empirical data and conceptual analysis, the chapters provide opportunities for theorising the work and working conditions of educational leaders alongside questions of compliance and resistance that further improve the understanding of these concepts in the field. Providing cutting-edge research and theorisation into this emerging area, the book will be highly relevant for researchers, academics and postgraduate students in the fields of educational leadership, management and administration, and educational policy. It will also be of interest to school leaders"--
Keywords: School administrators; Leadership -- Moral and ethical aspects; School management and organization; Resistance (Philosophy); Compliance; EDUCATION / Administration / General